2009
DOI: 10.1242/jcs.060913
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic chromosome interactions of Epstein-Barr nuclear antigen 1 (EBNA1) and human EBNA1-binding protein 2 (EBP2)

Abstract: by tethering the episomes to the cellular chromosomes in mitosis. A host nucleolar protein, EBNA1-binding protein 2 (EBP2), has been shown to be important for interactions between EBNA1 and chromosomes in metaphase and to associate with metaphase chromosomes. Here, we examine the timing of the chromosome associations of EBNA1 and EBP2 through mitosis and the regions of EBNA1 that mediate the chromosome interactions at each stage of mitosis. We show that EBP2 is localized to the nucleolus until late prophase, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 57 publications
3
59
2
Order By: Relevance
“…EBNA1 binds directly to viral DNA via its C-terminal domain and tethers the EBV genome to chromatin through its N-terminal domain, initially by direct interactions via its AT hooks, or afterwards through association with the nucleolar EBNA1 binding protein 2 (EBP2). The latter is a part of the perichromosomal layer and the binding with EBNA1 may be required to stabilize the EBNA1-chromosome interaction [149].…”
Section: Latent Dna Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…EBNA1 binds directly to viral DNA via its C-terminal domain and tethers the EBV genome to chromatin through its N-terminal domain, initially by direct interactions via its AT hooks, or afterwards through association with the nucleolar EBNA1 binding protein 2 (EBP2). The latter is a part of the perichromosomal layer and the binding with EBNA1 may be required to stabilize the EBNA1-chromosome interaction [149].…”
Section: Latent Dna Virusesmentioning
confidence: 99%
“…Murine leukemia virus (MuLV) (p12) [133,134] Human immunodeficiency virus (HIV) (LEDGF/p75) [141] Avian sarcoma virus (ASV) (IN) [132] Foamy virus (FV) (Gag) [143,144] Epstein Barr virus (EBV) EBNA1 [147][148][149] Kaposi sarcoma-associated herpesvirus (KSHV) LANA [151,152,154] Bovine (BPV) and human papillomavirus (HPV) E2 [155][156][157][158] Simian vacuolating virus 40 (SV40) unknown [161,162] …”
Section: Viruses Chromatin Tethering Factormentioning
confidence: 99%
“…LR2 or GR2 (residues 327-377) is also a Gly and Arg repeating unit. A host nucleolar protein, EBP2, associates with EBNA1 at GR1 and GR2, which might facilitate loading of EBNA1 onto mitotic chromosomes (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…Stable complex formation between EBNA1 and the nucleosome assembly proteins, NAP1 and TAF-I, can affect cellular DNA replication (309). The EBNA1 portion of the EBNA1-binding protein 2 complex was shown to promote its interaction with mitotic chromosomes (218). A recent study has demonstrated that high-level expression of the EBNA1 protein in NPC cells interferes with mitotic segregation (275).…”
Section: The Molecular Mechanisms Of Ebv Infection and The Effects Onmentioning
confidence: 99%